Gastropancreatic ligament: Description, incidence, and involvement during laparoscopic sleeve gastrectomy. Issue 3 (12th January 2017) - Rebibo, Lionel; Darmon, Ilan; Peltier, Johann; Dhahri, Abdennaceur; Regimbeau, Jean‐Marc
Abstract : During laparoscopic sleeve gastrectomy (LSG), adhesions between the stomach and the pancreas are sometimes found, forming a "gastropancreatic ligament" (GPL). However, the GPL has only been described once in the literature, in 1985. The objective of this study was to determine the incidence of the GPL during LSG, describe this structure and assess its effect on the surgical technique. All patients undergoing primary LSG in our institution ( n = 240) and patients referred for gastric fistula (GF) after primary LSG ( n = 18) between January 2015 and December 2015 were included. The primary endpoint was the incidence of a GPL during primary LSG. The secondary endpoints were the postoperative complication rate, the postoperative GF rate, and the presence of this ligament during reoperation for GF. Among the 240 patients, a GPL was visible in 49 cases (20.4%) and was described as thin in 34 of these (69.4%). Twelve postoperative complications (5%) were observed, including seven major (2.9%). The GF rate was 2% ( n = 5), not requiring reoperation. The gastric stenosis rate was 0.4% ( n = 1). The GPL had been previously sectioned in one of the five patients (20%) with postoperative GF. During the study period, 18 patients were referred for GF and 14 were reoperated. A non‐sectioned GPL, not described in the operating report, was observed in four patients (28.5%). A GPL was identified in 20.4% of cases. Identification of a GPL could be important in the context of LSG, as section of the ligament allows tension‐free stapling to be performed and can therefore possibly reduce the risk of postoperative complications, particularly GF. Clin. Anat. 30:336–341, 2017. © 2017 Wiley Periodicals, Inc.